KOMUNIKASI KESEHATAN PERILAKU HIDUP SEHAT #JSR DI MEDIA SOSIAL: Health Communication of Healthy Living Behavior #JSR On Social Media - Hindina Maulida; R Yogie Prawira W; Meydora Cahya Nugrahenti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2020)
Convincing people to have a healthy lifestyle is not easy, so it needs a particular approach, such as health communication. The study aims to examine health communication #JSR healthy lifestyle conducted by Dr. Zaidul Akbar through social media. The research method used in the study is descriptive qualitative, which is more focused on 'what' rather than 'how' and 'why' something happens. Data were obtained from interviews with #JSR users who actively listened, followed, and subscribed to studies of Dr. Zaidul Akbar on social media and observation on the official social media Dr. Zaidul Akbar, like the @zaidulakbar Instagram account, Dr. YouTube channel. Zaidul Akbar Official and Facebook @officialdrzaidulakbar. The results suggest that the source of healthy lifestyle #JSR is dr. Zaidul Akbar. Second, the message designed to grab audience attention with the picture attached, clear and relevant, provide benefit and risk information, arouse emotional and rational, consistent and transparent, and contain a call to action. Third, the media used are social media platforms, YouTube, Instagram, and Facebook, as social media with the four highest ranks that are most widely used by Indonesians. Fourth, effects on message recipients in the form of cognitive, affective, and behavioral effects.